“I wasn’t that good at it but I pretended to be”: Students’ Experiences of the Impostor Phenomenon in Academic Settings - Menard, Amy; Bondy, Michelle; Jones, Madison; Desjardins, Lauren; Milidrag, Lana; Foulon, Alanna; Chittle, Laura (Alberta Journal of Educational Research, 2023)
The impostor phenomenon (IP) is an internalized feeling of fraudulence characterized by beliefs that one’s personal successes are due to external factors (e.g., luck) rather than internal attributes. Individuals who suffer from impostor feelings may feel that they are not really intelligent or capable but have instead fooled others. Written descriptions of IP experiences were provided by 879 graduate and undergraduate students and submitted to content analysis. Nine major themes were identified across three categories: causes (i.e., novel experiences, challenges, everyday academic interactions, and high expectations), feelings and impact (i.e., negative psychophysiological symptoms and negative thoughts and emotions), and management (i.e., negative, neutral, and positive). Implications for addressing these feelings in post-secondary settings are considered. Keywords: higher education; individual differences; stress/coping; content analysis; qualitative research Le phénomène de l'imposteur (PI) est un sentiment de fraude intériorisé, caractérisé par la conviction que les succès personnels sont dus à des facteurs externes (par exemple, la chance) plutôt qu'à des attributs internes. Les personnes qui souffrent du sentiment d'imposture peuvent avoir l'impression qu'elles ne sont pas vraiment intelligentes ou capables, mais qu'elles ont plutôt trompé les autres. Des descriptions écrites d'expériences de PI ont été fournies par 879 étudiants de premier et deuxième cycles et ont été soumises à une analyse de contenu. Neuf thèmes principaux ont été identifiés dans trois catégories : les causes (expériences nouvelles, défis, interactions académiques quotidiennes et attentes élevées), les sentiments et l'impact (symptômes psychophysiologiques négatifs, pensées et émotions négatives) et la gestion (négative, neutre et positive). Les implications de la prise en compte de ces sentiments dans le cadre de l'enseignement post-secondaire sont examinées. Mots clés : enseignement supérieur ; différences individuelles ; stress/capacités d’adaptation ; analyse de contenu ; recherche qualitative